2017
DOI: 10.1080/00325899.2017.1288841
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of aging behaviour for aluminium powders during an atmosphere simulation of the LBM process

Abstract: Additive layer manufacturing (ALM) offers for production of parts and components for aeronautical applications potential cost benefits over conventional manufacturing routes. In particular, powder bed processes offer a high degree of design flexibility while enabling weight reduction due to topological optimisation. The quality and properties of the parts are strongly dependent on the powder quality which, in turn, is influenced by handling and storage of the powder. For this reasons an undefined contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…3). The results in [33] show that even for these very spherical particles an increasing humidity level leads to a significant decrease in the flowability of the powder (which in this work was concluded from an increase in the avalanche angle and avalanche time in a Revolution Powder Analyzer test). The reduced flowability is also in this work attributed to a higher agglomeration rate due to higher moisture content and hydrogen bonds.…”
Section: Moisture Pick-up Formation Of Liquid Bridges and The Role Of Oxidesmentioning
confidence: 56%
See 1 more Smart Citation
“…3). The results in [33] show that even for these very spherical particles an increasing humidity level leads to a significant decrease in the flowability of the powder (which in this work was concluded from an increase in the avalanche angle and avalanche time in a Revolution Powder Analyzer test). The reduced flowability is also in this work attributed to a higher agglomeration rate due to higher moisture content and hydrogen bonds.…”
Section: Moisture Pick-up Formation Of Liquid Bridges and The Role Of Oxidesmentioning
confidence: 56%
“…It could be argued that the observed high level of water absorption in AlSi10Mg, as compared to the three other powder alloys, is due to the less spherical shape of the particles in the AlSi10Mg powder used here. However, Bauer [33] investigated AlSi10Mg powder atomized by the Electrode Induction Melting Gas Atomization (EIGA) process, which resulted in a very spherical morphology. A moisturizing treatment at 23.7 °C and 84.2 % rH for 72 h was applied to the EIGA atomized powder, which is similar to the conditions applied in the present study (Fig.…”
Section: Moisture Pick-up Formation Of Liquid Bridges and The Role Of Oxidesmentioning
confidence: 99%
“…Especially aluminium powders (AlSi10Mg and Scalmalloy) were strongly affected compared to others (IN718 and Ti6Al4V) [1]. Bauer [2] reported similar findings for AlSi10Mg0.45 and AlSi7Mg0.6. In a follow-up paper Cordova et al [3] showed that moisture affected the layer density, but only to a strong degree for AlSi10Mg.…”
Section: Introductionmentioning
confidence: 63%
“…Similar studies have been completed for various types of aluminas; however, to the best of our knowledge we have not seen a study performed in situ with aluminum powders [14]. The ability to prepare aluminum powder surfaces for improved chemical receptivity is of interest to a wide variety of industrial, medical, and academic applications where the surface state is critical for the final product properties [15]. This is especially relevant in additive manufacturing where the powder is typically recycled [16].…”
Section: Introductionmentioning
confidence: 93%
“…Thermal treatment has been utilized to decompose these phases into the more reactive phase boehmite and to liberate the hydrogen bond surface hydroxyls. This is particularly relevant to metallurgical processing and additive manufacturing, where the surface hydroxides and oxides can interfere with the final product [28]; additionally, surface aging can interfere with flow properties impeding proper powder distribution [15].…”
Section: Introductionmentioning
confidence: 99%